PENGARUH LEADERSHIP, MOTIVATION DAN WORK DISCIPLINE TERHADAP EMPLOYEE PERFORMANCE PADA PEGAWAI SEKRETARIAT DPRD KOTA SURABAYA - Oktarina Nur Ar Rasyid (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to see the effect of leadership, motivation, and work discipline independently and simultaneously on the performance of the Regional Representative Assembly secretariat. The population used in this study were employees, totalling 50 employees. This study has three independent variables (leadership), motivation, and work discipline; the dependent variable is employee performance. The data is collected using a questionnaire. Then the data were analysed using multiple linear regression. This regression analysis indicates a significant influence between the independent variables. This study demonstrates that leadership, motivation, and work discipline have a positive and meaningful relationship with employee performance. Simultaneously, it is also known that there is a positive relationship between leadership, motivation, and work discipline on employee performance. This research is expected to have implications for considering the Regional Representative Assembly secretariat in improving employee performance. It implies that leaders consider decision-making to enhance employee performance. Improved employee performance in an agency can assist in assessing the overall performance of employees.